COVID-19 impact on mental health, healthcare access and social wellbeing – a black community needs assessment - Olihe Okoro; Elyse Carter Vosen; Kay Allen; Janet Kennedy; Renee Roberts; Taiwo Aremu (International Journal for Equity in Health, 2022)
Abstract Background The COVID-19 pandemic has had a disproportionate effect on the Black/African American population. In addition to the higher infection rates and the worse outcomes, there were other unintended consequences of the pandemic. The study objective was to determine the impact of COVID-19 on the Black/African American community. Methods A needs assessment was conducted using a mixed-methods approach. To address this specific study objective, an item included in the survey questionnaire asked respondents (n = 183) about their greatest worry related to CODID-19. Interviews and focus group discussions were conducted to further explore individual and community perceptions. Results The areas of greatest concern were Health (41.0%), Family (25.1%), Finances (8.2%), and Education (4.9%). The needs assessment revealed that the COVID-19 pandemic had a profound impact on the mental health and wellness, healthcare access and utilization, and social aspects of life the Black community. Emerging themes revealed that there was worsening mental health for many, limited healthcare access and under-utilization, and profound disruption of the social cohesive identity of the Black/African American community. Conclusion Pre-existing structural inequities are implicated in the mental health impact, as well as the under-utilization of and limited access to healthcare services in the Black/African American population. The impact on social well-being emphasizes the important role of culture in the population health of communities of color, further supporting the need for culturally-responsive public health interventions when targeting these communities.